2019
DOI: 10.1016/j.radcr.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Primary diffuse large B-cell non-Hodgkin's lymphoma of the breast—A case report and review of the literature

Abstract: Primary breast lymphoma (PBL) is considered a rare clinical entity forming about 0.4%-0.5% of all breast tumors.In this report we have presented a case of PBL in a 56-year-old female complaining of a mass in the upper medial quadrant of the breast.PBL suspicion of our case was made by breast radiology and the sure diagnosis was reached by the immunohistochemistry results; CD (cluster of differentiation) 20: was diffusely positive; Pan-CK (pan-cytokeratin): was diffusely negative in tumor cells. Hence, the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 10 publications
0
12
0
9
Order By: Relevance
“…Breast involvement with Hodgkin's disease or T-cell lymphomas is very rare [6] . Lymphoma arising from the breast occurs almost exclusively in women [7] . Some studies have proposed probable relation to estrogen for this occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast involvement with Hodgkin's disease or T-cell lymphomas is very rare [6] . Lymphoma arising from the breast occurs almost exclusively in women [7] . Some studies have proposed probable relation to estrogen for this occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have proposed probable relation to estrogen for this occurrence. Smaller series have reported that lymphoma arising from the breast occurs more commonly in the right breast [7] . The rarity of this cancer is because the breast contains less lymphoid tissue than other organs, such as the intestines and lungs, where primary lymphomas are more common [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Immunochemotherapy combined with consolidative whole ipsilateral breast radiotherapy is the major treatment for PBL [9,13], while surgical treatment offers no benefit to outcomes [14]. Therefore, patients in our study underwent excisional biopsies rather than further surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary lymphadenopathy is often found, NHL should also be suspected when lymphadenopathy is in an unusual lymph node area such as inguinal, however, our patient did not have lymphadenopathy other than the homolateral axillary lymph node. Only histological examination of the tissue, preferably by echo-guided biopsy puncture, can confirm the diagnosis of NHL [1]. Generally, the diagnosis of NHL is easy, but there are certain points which deserve to be underlined: the mammary lymphoma does not offer any histological characteristic because of its localization; the extemporaneous study involves a significant risk of error; mastectomy right away is to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Primary non-Hodgkin's lymphoma of the breast (PNHL) is a rare entity, accounting for approximately 0.04% to 0.5% of all malignant breast tumors and forming approximately 1.7% to 2.2% of Extra-ganglionic NHL [1] [2] [3]. Their heterogeneity is reflected by various clinical, morphological, immunological and cytogenetic presentations which explain their different classifications.…”
Section: Introductionmentioning
confidence: 99%